KEANEKARAGAMAN TANAMAN ANGGREK DI DESA SENGKOL, KECAMATAN PUJUT, KABUPATEN LOMBOK TENGAH - Slamet Mardiyanto Rahayu; M. Ali Azis Hasan Rizki; Syuhriatin, Syuhriatin (Nusantara Hasana Journal, 2025)
Lombok is one of the island in the Lesser Sunda Islands. This island has high biodiversity, one of which is orchids. Orchids are a group of epiphytic plants that are in great demand because of the beauty of their flowers. This research aims to determine the diversity of orchid species in Sengkol Village, Pujut District, Central Lombok Regency. The research was carried out using an exploration method followed by species identification based on morphological characteristics. Based on research, it was found that two species of orchids were used as ornamental plants in Sengkol Village, namely: Phalaenopsis pulcherrima (Lindl.) J.J.Sm. and Vanda coerulea Griff. ex Lindl.